STUDENTS' PERCEPTIONS OF 'BRAIN DECAY' CONTENT ON THE TIKTOK ACCOUNT @CNNINDONESIA - Wulansari, Fitri Retno; Aesthetika, Nur Maghfirah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: 'brain rot' presented through the content of @cnnindonesia TikTok account. Using qualitative methods and phenomenological approaches, this study explores students' subjective experiences in consuming digital content and how Joseph A. DeVito's theory of perception can explain the way they shape their understanding of the phenomenon. Method: The data was collected through in-depth interviews with five informants who were active students, aged 18-25, had a TikTok account, and had followed @cnnindonesia account. Results: Based on the findings, student perceptions. 'Brain decay' is formed through a five-stage process, with the interpretation-evaluation stage being the most important. The informants agreed that this phenomenon is real among students, characterized by a decrease in critical thinking skills and a tendency to avoid in-depth content due to excessive consumption of 'dime' content. Nonetheless, content @cnnindonesia spark strong self-awareness, encourage students to be more selective in choosing content, limit the duration of social media use, and retrain focus. Novelty: The conclusion of this study emphasizes the importance of digital literacy and self-awareness to overcome the negative impact of 'brain decay' content.